Privacy-Preserving Boolean Range Query With Temporal Access Control in Mobile Computing - Tong, Qiuyun; Li, Xinghua; Miao, Yinbin; Liu, Ximeng; Weng, Jian; Deng, Robert H. (IEEE transactions on knowledge and data engineering, 2023)
With increasingly popular GPS-equipped mobile devices (e.g., smartphones, tablets, laptops), massive spatio-textual data has been outsourced to cloud servers for storage and analysis such as spatial keyword search. However, existing privacy-preserving spatial keyword query schemes only support coarse-grained non-temporal access control in single user sharing scenario, which does not scale well in time-related scenes such as message valid period. To solve the above issues, we propose P rivacy-preserving B oolean R ange Q uery with T emporal access control in mobile computing (PBRQ-T). Specifically, we first achieve PBRQ with linear search complexity using the adapted Gray code, Bloom filter, and Katz-Sahai-Waters encryption. Then, we provide fine-grained and temporal access control in PBRQ based on the forward/backward derivation function and attribute-based encryption, where PBRQ is executed only when the spatio-textual data is accessible. Finally, an enhanced PBRQ-T (i.e., PBRQ-T ^+ +<inline-graphic xlink:href="tong-ieq1-3152168.gif"/> ) with faster-than-linear search complexity is proposed by constructing a Quadtree index structure. Our formal security analysis shows that data privacy and index privacy can be guaranteed during the query process. Our extensive experiments using a real-world dataset demonstrate the efficiency and feasibility of our schemes.